Cotejo por superposición de huellas dactilares usando el programa Adobe PhotoShop - Solana Aguilar, Enrique (Archivos de criminología, seguridad privada y criminalística, 2021)
The main objective of this research was to present a manual that will allow us to have an auxiliary technique for comparing fingerprints by superimposing them, thus allowing the fingerprints to be visualized one below the other and thus making a causal and explanatory comparison, that would give the judge or the fingerprint researcher himself a more direct idea of the study that he is doing, and with this have a more accurate vision of what was being compared. This technique is proposed for fingerprints and addressed in a special way to those fingerprints latents that could be fixed only in a photographic way, thus achieving a fingerprint that could be compared by superimposing it with the existing control. For this manual, the Adobe PhotoShop program was used as a platform or computational tool. As a result, it was possible to obtain a manual that helps to compare footprints by superimposing them, which was validated and can serve as an auxiliary option for the comparison of footprints, marks, objects or any activity that requires a visual examination, simple and practical